Esterification of Free Fatty Acids Derived from Waste Cooking Oil with Octanol: Process Optimization and Kinetic Modeling. Issue 4 (3rd February 2016) - Chowdhury, Avisha; Sarkar, Debasish; Mitra, Debarati
Abstract: The synthesis of lubricant‐grade ester using waste cooking oil (WCO) as the primary feedstock is characterized in detail and optimized. WCO was initially hydrolyzed using Candida rugosa lipase to convert triglycerides into free fatty acids (FFA). Subsequently, the FFA were esterified with octanol by a heterogeneous catalytic reaction in batch mode. Both the hydrolysis and esterification steps were optimized in terms of relevant process parameters, employing the well‐known response surface methodology. The final product was characterized by Fourier transform infrared and nuclear magnetic resonance spectroscopy. Moreover, a pseudo‐homogeneous, second‐order kinetic model was proposed and validated with respect to the transient conversion data for the esterification reaction under optimum operating conditions. The overall output of the present study is highly useful in the design and development of large‐scale industrial flow reactors to produce biolubricant components using a domestic waste material as feedstock. Abstract : Response surface methodology was applied to optimize both the hydrolysis and esterification steps in the synthesis of a lubricant‐grade ester using waste cooking oil as the primary feedstock. A pseudo‐homogeneous second‐order kinetic model is proposed and validated with respect to the conversion data for the esterification reaction obtained under the determined optimum operating conditions.